Magnitude of blood pressure change and clinical outcomes after thrombectomy in stroke caused by large artery occlusion. (19th March 2021) - Anadani, Mohammad; Matusevicius, Marius; Tsivgoulis, Georgios; Peeters, André; Nunes, Ana Paiva; Mancuso, Michelangelo; Roffe, Christine; de Havenon, Adam; Ahmed, Niaz
Abstract: Background: Extremes of both high and low systolic blood pressure (SBP) after mechanical thrombectomy (MT) in large artery occlusion stroke are known predictors of unfavorable outcome. However, the effect of SBP change (∆SBP) during the first 24 h on thrombectomy outcomes remains unclear. We aimed to investigate the association between ∆SBP at different time intervals and thrombectomy outcomes. Methods: We analyzed MT‐treated patients registered in the SITS International Stroke Thrombectomy Registry from January 1, 2014 to September 3, 2019. Primary outcome was 3‐month unfavorable outcome (modified Rankin scale scores 3–6). We defined ∆SBP as the mean SBP of a given time interval after MT (0–2, 2–4, 4–12, 12–24 h) minus admission SBP. Multivariable mixed logistic regression models were used to adjust for known confounders and center as random effect. Subgroup analyses were included to contrast specific subpopulations. Restricted cubic splines were used to model the associations. Results: The study population consisted of 5835 patients (mean age 70 years, 51% male, median NIHSS 16). Mean ∆SBP was −12.3, −15.7, −17.2, and −16.9 mmHg for the time intervals 0–2, 2–4, 4–12 h, and 12–24 h, respectively. Higher ∆SBP was associated with unfavorable outcome at 0–2 h (odds ratio 1.065, 95% confidence interval 1.014–1.118), 2–4 h (1.140, 1.081–1.203), 4–12 h (1.145, 1.087–1.203), and 12–24 h (1.145, 1.089–1.203), for every increase of 10 mmHg. Restricted cubic spline models suggested that increasing ∆SBP was associated with unfavorable outcome, with higher values showing increased risk of unfavorable outcome. Conclusion: SBP increase after thrombectomy in large artery occlusion stroke is associated with poor functional outcome. Abstract : In acute ischemic stroke patients treated with mechanical thrombectomy, systolic blood pressure (SBP) change from baseline is associated with poor functional outcome. The association between SBP change and poor outcome was mostly linear; however, increasingly worse outcomes were observed for increasing SBP.